Public Banks and Public Water in the Global South: Financing Options for Sustainable Development - Thomas Marois; David A. McDonald; Susan Spronk (Routledge, 2025)
This volume presents the first systematic review of public bank lending in the water sector in the Global South. Many public banks have an explicit mandate to finance public water management, yet despite a resurgence of interest in public banks and the role they can play in sustainable development, their role in funding water management has been largely ignored. Drawing on case studies from Asia, Africa and Latin America, this book measures the scale and nature of interaction between public banks and public water operators for the provision of safe drinking water and sanitation. It identifies challenges and opportunities for deeper engagement between public banks and public water operators in the Global South and highlights promising practices, showcasing how these might be transferred to different regions and different sectors. Each case study is based on in-depth interviews with public banks that have funded public water operators, and public water operators that have borrowed from public banks, including Banco Popular in Costa Rica, the Development Bank of the Philippines, the National Bank for Agricultural and Rural Development in India and the TIB Development Bank in Tanzania. Overall, this book provides a critical analysis of the potential of public banks to address global water security issues. This book will be of great interest to students and scholars of water resource management, water and health, sanitation and sustainable development. It will also be of interest to professionals and policymakers working with public and development banks in the supply of safe water and sanitation for all. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.
Keywords: 330; Water; Water Resource Management; Sanitation; Water Security; Water and Health; Sustainable Development; Sustainable Development Goals; Global South; Public Water; Public Banks; Public Finance; Development Bank; The Municipal Services Project; Water Sector; Development Banking Associations; Banco Popular; FINDETER; National Bank for Economic and Social Development; FONPLATA; Landbank of the Philippines; Development Bank of the Philippines; Vietnam Development Bank; National Bank for Agricultural and Rural Development